2015
DOI: 10.3171/2015.5.peds14532
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric hydrocephalus: 40-year outcomes in 128 hydrocephalic patients treated with shunts during childhood. Assessment of surgical outcome, work participation, and health-related quality of life

Abstract: OBJECT Treatment for hydrocephalus has not advanced appreciably since the advent of CSF shunts more than 50 years ago. The outcome for pediatric patients with hydrocephalus has been the object for several studies; however, much uncertainty remains regarding the very long term outcome for these patients. Shunting became the standard treatment for hydrocephalus in Norway during the 1960s, and the first cohorts from this era have now reached middle age. Therefore, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 16 publications
7
59
0
2
Order By: Relevance
“…Better nutritional intake, usage of folic acid supplement before and during early pregnancy, amniocentesis, and screening for alpha-fetoprotein may also have been contributing factors [9, 10]. The gradual decreasing number of shunted individuals with NTD in our three cohorts from the 1960s, the 1980s and further, or until today corroborate with their findings [6, 7]. …”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Better nutritional intake, usage of folic acid supplement before and during early pregnancy, amniocentesis, and screening for alpha-fetoprotein may also have been contributing factors [9, 10]. The gradual decreasing number of shunted individuals with NTD in our three cohorts from the 1960s, the 1980s and further, or until today corroborate with their findings [6, 7]. …”
Section: Discussionsupporting
confidence: 79%
“…At the same time, in the cohort from the twenty-first century, we found a higher proportion of hydrocephalus associated with CNS tumor compared with our previous series [6, 7]. Some studies have found a gradual increase in the incidence of pediatric brain tumors during the last decades [13].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Besides the surgical letality (approx-Open Journal of Modern Neurosurgery imately 8%), the mortality rate over 20 years of follow-up has been reduced from 39% in the 1960s to 21% in the 1980s for patients without a tumor as underlying disease [50] [51]. Many patients present with neurologic deficits such as motor, visual or auditory impairment, and a huge number of deaths is due to delayed diagnosis of CSF diversion malfunction, regardless whether a shunt implantation or an endoscopic fenestration have been performed [11] [43].…”
Section: Long-term Resultsmentioning
confidence: 99%